On the Friction Stir Processing of Additive‐Manufactured 316L Stainless Steel. Issue 10 (10th May 2022) - Sajadifar, Seyed Vahid; Hosseinzadeh, Ali; Richter, Julia; Krochmal, Marcel; Wegener, Thomas; Bolender, Artjom; Heidarzadeh, Akbar; Niendorf, Thomas; Yapici, Guney Guven
Abstract : The novel combination of friction stir processing (FSP) and additive manufacturing (AM) is studied herein. Laser‐based powder bed fusion of metals (PBF‐LB/M) is used to establish 316 L stainless steel with a bimodal microstructure. Upon FSP, the as‐built bimodal microstructure with an average grain size of 179 μm is transformed into the unimodal microstructure containing ultrafine grains with an average grain size of 1.2 μm. Results obtained by mechanical testing reveal that after FSP; the hardness, the yield point, and the ultimate strength of additively manufactured 316 L are enhanced by 45%, 77%, and 62%, respectively. Microstructure assessment reveals that such a unique improvement in the mechanical properties is due to considerable structural refinement leading to grain boundary strengthening. Energy‐dispersive X‐Ray diffraction analysis reveals that phase transformation does not occur upon FSP. Fracture analysis further indicates that severe plastic deformation (SPD) during FSP can promote the transformation of coarse voids to fine voids and, hence, densification of as‐built parts. Abstract : This work highlights the utilization of friction stir processing for the surface modification of additive manufactured 316 L stainless steel. Mechanical behavior and microstructural evolution were exploited to establish the process–microstructure–property relationships in the severely deformed alloy. Provision of an ultrafine grained microstructure demonstrates the potential of severe plastic deformation as a post–processing tool for improved mechanical properties in additive–manufactured parts.